Frequency of Class I Anti HLA Alloantibodies in Patients Infected by HIV 1 - Leite, Elza Regina Manzolli (2010)
The aim of this study was to evaluate the presence of class I anti-HLA alloantibodies in patients infected by HIV-1 and relate it with the different clinical courses of the disease. Blood samples were collected in EDTA tubes from 145 individuals. HIV-1 infection was confirmed by ELISA test. The presence of class I anti-HLA alloantibodies and HLA allele’s were determined. Clinical evolution was set as fast (<1 year between diagnostic and death), moderate (1-3 years) or slow (>3 years). Class I anti-HLA alloantibodies presence was lower in healthy individuals than in those infected by HIV-1 (4.2% against 32.4%). However, an equal distribution of these alloantibodies was found among the individuals infected, independent on the clinical evolution. Thus, class I anti-HLA alloantibodies was not a determinant factor for patient worsening.